Osteonecrosis of the jaw during biyearly treatment with zoledronic acid for aromatase inhibitor associated bone loss in early breast cancer: A literature review - Kourie, Hampig Raphael (J Bone Oncol, 2015)
Osteonecrosis of the jaw (ONJ) is one of the most relevant and specific complication of biphosphonates. ONJ in patients receiving zoledronic acid every 3 to 4 weeks is frequently described, but the ONJ biyearly regimen used to reduce aromatase inhibitor associated bone loss (AIBL), is rarely reported. A literature review, focusing on the important trials using zoledronic acid to reduce AIBL, found that the mean risk of developing ONJ when zoledronic acid is used biyearly varies between 0.12% and 0.7%.